FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT NASABAH DALAM MEMILIH PEMBIAYAAN AKAD MURABAHAH (Studi Kasus Pada Bank Aceh Syariah Cabang Pembantu Idi Rayeuk) - febi febi; Junaidi Junaidi; Ade Fadhillah; Hayaturridha Hayaturridha (JIM: Jurnal Ilmiah Mahasiswa, 2019)
This study aims to determine what factors influence the interest of customer in choosing murabahah contract financing at Aceh Sharia Bank Idi Rayeuk Assistant Branch, and how these factors partially and simultaneously effect the interest of the customers. The research is a kind of quantitative research with descriptive research approach. For determination of sample, it was used probabiliy sampling technique with random sampling method. Meanwhile, to determine the sample size, by using Slovin formula, it was obtained 88 respondents as the research sample. Moreover, in data collection, the study refers to two primary data sources (data obtained through questionnaires distribution of 34 items of questions assessed by using likert scale), and secondary data (data obtained through decumantation). The data gained was in the feasibility test by using the test of validity, reliability, and the test of classical assumptions. Then, to examine the hypothesis, it was used multiple regression analysis test that includes the determination test, F test and t test. Eventually, the research results showed that simultaneously the factors of service, location, and promotion have positive and significant effect to customers’ interest in choosing murabahah contract funding. In addition, partially at the same time it indicates that service and promotion also have positive and significant influence to the customers’ interest. It is proven by looking at sig value <0,05 (0,020<0,05) for service and 0,019<0,05 for promotion, whereas, the factor af location does not have significant effect to the customers’ interest to choose murabahah contract financing proved by sig value >0,05 (0,364>0,05).